Temporal stability of bacterial symbionts in a temperate ascidian - López-Legentil, Susanna; Turon, Xavier; Espluga, Roger; Erwin, Patrick M. (Frontiers in Microbiology, 2015)
In temperate seas, both bacterioplankton communities and invertebrate lifecycles follow a seasonal pattern. To investigate whether the bacterial community associated with the Mediterranean ascidian Didemnum fulgens exhibited similar variations, we monitored its bacterial community structure monthly for over a year using terminal restriction fragment length polymorphism (T-RFLP) and clone library analyses of 16S rRNA gene sequences. D. fulgens harbored a bacterial consortium typical of ascidians, including numerous members of the phylum Proteobacteria, and a few members of the phyla Cyanobacteria and Acidobacteria. The overall bacterial community in D. fulgens had a distinct signature from the surrounding seawater and was stable over time and across seasonal fluctuations in temperature. Bacterial symbionts were also observed around animal cells in the tunic of adult individuals and in the inner tunic of D. fulgens larvae by transmission electron microscopy. Our results suggest that, as seen for sponges and corals, some species of ascidians host stable and unique bacterial communities that are at least partially inherited by their progeny by vertical transmission.